The Gly103Arg variant in hereditary transthyretin amyloidosis - Xiong, Yihan; Qu, Gongcheng; Lu, Xiaoyu; Chang, Xin; Zhang, Miaoping; Liang, Jiantang; Lin, Kexing; Zhao, Xiaoman; Fu, Xuejun; Huang, Ying; Xu, Qianhui (Frontiers in Neurology, 2024)
Background Hereditary transthyretin amyloidosis (ATTRv) is an autosomal dominant inherited systematic disease primarily affecting the peripheral and autonomic nervous system, heart, eyes and kidney. Over 140 variants have been identified worldwide, with the Gly103Arg variant reported exclusively in China. This variant is characterized by early onset eye manifestations, making accurate and timely diagnosis difficult. Therefore, we conducted a case study and literature review to investigate the clinical characteristics of the Gly103Arg variant in hereditary transthyretin amyloidosis. Methods We identified three patients and an asymptomatic carrier in a four-generation family by sequencing the TTR gene. The proband underwent a lumbar puncture, electromyography, abdominal fat biopsy, among other tests. Case reports of Gly103Arg variant were retrieved through a literature search for an analysis of clinical characteristics. Results The study included clinical data of 44 patients. Our literature review collected data on 41 patients and the present report supplied 3 patients with the Gly103Arg variant. The mean age at onset was 39.1 ± 4.27 years (range 30–47 years) with a female ratio of 52.3%. All cases were reported in China, predominantly in southern regions, especially Yunan and Guizhou Provinces. The initial manifestation was blurred vision, except for one case presenting with numbness in the upper extremities. All of them had vitreous opacity; 17 cases had peripheral neuropathy,6 cases had autonomic neuropathy, and 3 cases had cardiopathy. No disease-related deaths have been reported to date. Conclusion The Gly103Arg variant is unique to the Chinese population, frequently occurring in southern China. The main clinical manifestations are blurred vision, vitreous opacity, and neuropathy, with cardiopathy being rare. ATTRv should be considered if a patient diagnosed with CIDP does not respond to related therapy. Abdominal fat biopsy is a convenient and accurate diagnostic method.